2022
DOI: 10.1029/2021jd036013
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Future AR Count and Size: Overview of the ARTMIP Tier 2 CMIP5/6 Experiment

Abstract: The Atmospheric River (AR) Tracking Method Intercomparison Project (ARTMIP) is a community effort to systematically assess how the uncertainties from AR detectors (ARDTs) impact our scientific understanding of ARs. This study describes the ARTMIP Tier 2 experimental design and initial results using the Coupled Model Intercomparison Project (CMIP) Phases 5 and 6 multi‐model ensembles. We show that AR statistics from a given ARDT in CMIP5/6 historical simulations compare remarkably well with the MERRA‐2 reanalys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 109 publications
(214 reference statements)
4
62
0
Order By: Relevance
“…One should note that the use of time-dependent thresholds can automatically remove the effect of increased background moisture caused by global warming, because the IVT threshold is defined by percentile calculated in space rather than in time. O'Brien et al (2021) found that the ARs detected by these two algorithms behave differently from other algorithms in a warmer climate (see discussion in Section 3.4). While the main focus is the fixed IVT threshold used in Mundhenk et al (2016), we also discuss ToE sensitivity to these different algorithms and the impact of time-dependent thresholds in Section 3.4.…”
Section: Ar Detectionmentioning
confidence: 94%
“…One should note that the use of time-dependent thresholds can automatically remove the effect of increased background moisture caused by global warming, because the IVT threshold is defined by percentile calculated in space rather than in time. O'Brien et al (2021) found that the ARs detected by these two algorithms behave differently from other algorithms in a warmer climate (see discussion in Section 3.4). While the main focus is the fixed IVT threshold used in Mundhenk et al (2016), we also discuss ToE sensitivity to these different algorithms and the impact of time-dependent thresholds in Section 3.4.…”
Section: Ar Detectionmentioning
confidence: 94%
“…Although global metrics are presented in this work, the primary purpose is to provide quality control between Tier 1 (MERRA‐2 Reanalysis, herein referred to as T1‐MERRA‐2) and Tier 2 (T2‐HR model simulations) as well as context for other ARTMIP experiments, both reanalysis and CMIP5/6 experiments (O’Brien et al., 2022; Collow et al., 2022). Although O’Brien et al.…”
Section: Data and Approachmentioning
confidence: 99%
“…Furthermore, we acknowledge that AR statistics may depend on detection algorithms, and IVT-magnitude-based methods have limitations to detect and track ARs globally. Various AR detection algorithms show different pros and cons (Collow et al, 2022;O'Brien et al, 2022;Shields et al, 2018). To examine the detection algorithm dependency issue, we also tracked ARs using the TEMPEST algorithm (McClenny et al, 2020), which is one of the algorithms in the AR tracking method intercomparison project (ARTMIP) (Shields et al, 2018).…”
Section: Ars Detection Algorithmmentioning
confidence: 99%